Pengaruh Review Produk Dan Promosi Terhadap Keputusan Pembelian Scarllet Pada Mahasiswa Pendidikan Ekonomi Universitas HKBP Nommensen Pematang Siantar TA 2023/2024 - Elisabet Pretty Sitorus; Binsar Tison Gultom; Injen Pardamean Butarbutar (JOURNAL SAINS STUDENT RESEARCH, 2023)
The purpose of this research is to determine the influence of Product Reviews and Promotions on Scarlett purchasing decisions among Economic Education Students at HKBP Nommensen University, Pematang Siantar. This research is quantitative. The sampling technique used purposive sampling of 100 people and the measurement scale used a Likert scale. Data analysis uses multiple regression tests with the SPSS 25 program. Based on the calculation results, it shows that the product review variable partially has an influence on purchasing decisions, namely 2.215, and the promotion variable partially has an influence on purchasing decisions of 4.608. Meanwhile, the two variables simultaneously have an influence on purchasing decisions of 31.396. This means that the better product reviews and promotions will lead to higher purchasing decisions and will therefore increase the level of customer loyalty.